The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1088/1757-899x/702/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of process parameters for bioethanol production from oil palm frond juice by Saccharomyces cerevisiae using response surface methodology as a tool

Abstract: The aim of this research was to investigate the effect of temperature, medium initial pH and rotation rate on the production of bioethanol from OPF juice without nutrient and nitrogen source supplementation using Saccharomyces cerevisiae Kyokai No. 7 (ATCC 26622). A five-level-three-factor central composite design (CCD) was employed in this study and the central point of each process variable was chosen based on the best condition obtained from the one-factor-at-time (OFAT) method. The parameters ranges were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Maximum bioethanol concentrations have been obtained under similar conditions (Betiku and Taiwo, 2015;Zani et al, 2019). However, the concentrations obtained were higher than those of Sivamani and Baskar (2018) and Dasgupta et al (2013), with 25.59 g/L and 17.44 g/L, respectively, after similar optimization experiments.…”
Section: 42mentioning
confidence: 65%
“…Maximum bioethanol concentrations have been obtained under similar conditions (Betiku and Taiwo, 2015;Zani et al, 2019). However, the concentrations obtained were higher than those of Sivamani and Baskar (2018) and Dasgupta et al (2013), with 25.59 g/L and 17.44 g/L, respectively, after similar optimization experiments.…”
Section: 42mentioning
confidence: 65%
“…According to reports, a Central Composite design was successfully used to optimize the parameters of a process that was used for the production of bioethanol by a yeast strain (ZANI et al, 2019). Other studies indicated that CCR designs were also effectively applied in the evaluation of performance and optimization of the parameters of an anaerobic codigestion of leachate and glycerol for renewable energy generation, and in the maximization of the phytoremediation process of an arsenic-contaminated water (DE SOUZA et al, 2019;TAKEDA et al, 2020).…”
Section: Central Composite Rotational Designsmentioning
confidence: 99%
“…In recent years, bioenergy production from various biomass sources has received a lot of attention, and perennial grasses have emerged as a potential source of biomass for biofuel production [1][2][3]. There is less competition for food crops when perennial plants are cultivated on land that is no longer suitable for agricultural use [4,5].…”
Section: Introductionmentioning
confidence: 99%